The digital economy, global tax reforms and developing countries: An evaluation of Pillar I and Art. 12B UN Model - Jost H. Heckemeyer; Inga Schulz; Christoph Spengel; Sarah Winter (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
This paper evaluates the Multilateral Convention to implement Pillar I Amount A, released by the OECD in October 2023, and the alternative proposal of Art. 12B for tax treaties suggested by the UN, with a particular emphasis on the perspective of developing countries. We conduct a comparative analysis of the proposals using an integrated economic and legal approach. Our assessment is based on the two proposals' ability to generate tax revenue and their implications for net-importing countries. Our legal analysis demonstrates significant differences between the two proposals in the implied reallocation of taxing rights, depending on the considered (digital) business model. Interestingly, we find that overall and despite its complexity, Pillar I Amount A addresses the specific interests of developing countries better than Art. 12B UN Model. In particular, Pillar I Amount A will likely outperform the UN's proposal in terms of its tax revenue potential.
Keywords: F23; H25; H32; K34; 330; Digital Economy; Corporate Tax; Global Tax Reform; OECD Pillar 1; Developing Countries